Modeling And Optimization Of Solvent-Free Isoamyl Acetate Production Via Enzymatic Esterification - Yusoff Azudin, Nurhazwani (2014)
Isoamyl acetate is an organic compound listed under the esterfamily, and used as flavor additive especially in food industries. Studies on esterification processes begin with traditional extraction of ester from plants,followed by chemical synthesis route. Nowadays, the esterification process has shifted to biocatalytic flavor due to consumer's inclination towards natural compared to chemical resources. Thisstudy was carried out to examine the reaction synthesis between acetic anhydride and isoamyl alcohol in the presence of Candida antarctica Lipase-B (CALB) as a catalyst in solvent-free system (SFS). Results show that two reactions took place: (i) between acetic anhydride and isoamyl alcohol, and (ii) between acetic acid and isoamyl alcohol. Effect of different reaction parameters on the final yield of isoamyl acetate, and optimization of process parametersusing a statistical tool were also investigatedwithresponse surface methodology (RSM).